The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s10068-018-0418-x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of dry and wet aging on physicochemical and sensory characteristics of pork loin with two aging times

Abstract: This study investigated the effects of aging methods (wet aging and dry aging) and aging times (7 and 14 days) on the physicochemical and sensory characteristics of meat quality using pork loin. Dry-aged loin (DA) had significantly lower moisture content and higher crude fat protein content than wet-aged loin (WA). The pH of DA was significantly higher than that of WA and it increased with the aging time. DA showed lower cooking loss and higher aging loss than WA (p \ 0.001). Lipid oxidation and metmyoglobin c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 32 publications
2
9
1
Order By: Relevance
“…Lower moisture has been associated with less surface moisture availability, leading to a decrease in light reflection and thus resulting in a darker appearance [12]. These findings are in agreement with previous pork dry-aging studies, where higher initial lightness in wet-aged products compared to dry-aged products was reported [20,22,39]. While changes in color and color stability could be detrimental, studies have reported that pork consumers preferred darker-colored chops over lighter-color chops [43][44][45], suggest-ing potential dry-aging benefits during retail settings.…”
Section: Display Color Stabilitysupporting
confidence: 91%
See 3 more Smart Citations
“…Lower moisture has been associated with less surface moisture availability, leading to a decrease in light reflection and thus resulting in a darker appearance [12]. These findings are in agreement with previous pork dry-aging studies, where higher initial lightness in wet-aged products compared to dry-aged products was reported [20,22,39]. While changes in color and color stability could be detrimental, studies have reported that pork consumers preferred darker-colored chops over lighter-color chops [43][44][45], suggest-ing potential dry-aging benefits during retail settings.…”
Section: Display Color Stabilitysupporting
confidence: 91%
“…Consequently, more crust loss was also observed from both DA and UDA loins compared to WA loins (p < 0.05). A decrease in product yields from dry-aged treatments has been constantly reported in previous studies (though predominantly dry-aged beef) [12,20,36]. The substantial decrease in yield is expected, mainly due to the moisture evaporation during the dry-aging process and the removal of the dehydrated surfaces (crust) following the aging process.…”
Section: Processing Loss and Total Yieldmentioning
confidence: 58%
See 2 more Smart Citations
“…For measuring cooking loss, samples were packed in polyethylene bags (150 × 200, PA/PE 90) and cooked in a waterbath (WNB45, Memmert GmbH + Co. KG, Schwabach, Germany) maintained at 82 °C until the core temperature of meat samples reached up to 72 °C [ 29 ] as recorded by digital food thermometer (TP101; temperature range of −50 °C to 300 °C). The weight of the initial raw meat sample and the cooked sample was recorded by digital compact weighing balance (SF-400, 7000 g ± 1 g, Zhejiang Tiansheng Electronic Co., Ltd., Zhejiang, China); the cooking loss was calculated using the following formula [ 30 ]. Cooking Loss (%) = w1 − w2/w1 × 100 where w1 = weight of steak before cooking, and w2 = weight of steak after cooking.…”
Section: Methodsmentioning
confidence: 99%